Kesalahan Pemakaian Ejaan dan Diksi pada Media Luar Ruang di Kota Palangka Raya - Yanesupriana Yanesupriana; Albertus Purwaka; Indra Perdana; Denny Frianto; Riwi Nitiya (Universitas Palangka Raya, 2022)
This study aims to describe (1) spelling mistake on banners and billboards in the city of Palangka Raya, (2) describe diction mistake on banners and billboards in the city of Palangka Raya. This study is a qualitative research. Qualitative research is used to describe the mistakes in the use of spelling and diction on banners and billboards in the city of Palangka Raya. Based on the results of the data analysis of spelling and diction mistakes on banner and billboards in the city of Palangka Raya, there are 55 language mistakes, the dominant data is the data of spelling mistake from the use of diction mistake data. There are 36 data of spelling mistake, and 19 data of diction usage mistake. The results of the analysis based on the formulation of the problem are as follows. First, the mistake in the use of spelling that were analyzed were 36 data. There are 20 data of spelling mistakes on banners and there are 16 data of spelling mistakes on billboards. Second, there were 19 data that were analyzed in the mistakes of diction. There are 8 data of diction mistakes on banners, and 11 data diction mistakes on billboards.